STRATEGI PEMASARAN YANG EFEKTIF UNTUK UMKM DESA MUNGGUR - Wardono, Mochammad Taufik Nur Sapto; Al Farisi, Salman; Mahmudah , Luthfi (AL HAZIQ: Journal of Community Service, 2025)
This Community Service Program (PKM) aims to enhance the capacity of MSME actors and students in understanding and applying effective marketing strategies in Munggur Village. The program is driven by the low utilization of digital technology and the limited understanding of modern marketing among local MSME operators. The training involved 40 participants consisting of MSME practitioners and student facilitators. The implementation methods included field observation, development of training modules, interactive workshops, technical demonstrations, hands-on digital content creation, and evaluations through pre-tests, post-tests, and short interviews. The results indicate significant improvement in participants’ abilities to create unique products, define advertising objectives, implement digital marketing, build consistent branding, utilize e-commerce, and enhance customer service quality. Participants were also able to produce basic promotional content and began using social media as a marketing tool. Overall, this PKM activity has had a positive impact on increasing digital marketing literacy and entrepreneurial competence, thereby supporting the sustainable development of MSMEs in Munggur Village.